DEVELOPMENT OF COMIC MEDIA MATERIAL DETERMINING CHARACTER AND CHARACTER OF FAIRY TALES FOR CLASS 4 PRIMARY SCHOOL STUDENTS - Pratama, Dimas Ramzy; Mujiwati, Endang Sri; Putri, Kharisma Eka (JURNAL EDUSCIENCE, 2023)
The The background of teacher when conveying material on determining characters and fairy tale characters in using learning media is still less varied. The teacher only uses thematic book teaching materials by displaying pictures and stories about fairy tale characters and characters, so that students do not understand the material presented. The formulation of the problem is how the validity, effectiveness, teacher and student responses to comic media material determine the characters and characters of fairy tales for grade 4 elementary school students in their use as media during learning. This study uses the Research and Development (R&D) research method with the ADDIE model (Analyze, Design, Developmen, Implementation, and Evaluation). The subjects of this study were teachers and fourth grade students at SDN Ngadi. The results of the comic media development research are as follows: (1) The validation results for comic media if we calculate the average result of 87.7% which is declared very valid. (2) The results of the effectiveness of comic media in the limited trial obtained 100% while the wide trial obtained 94.11%, based on these results, the comic media was stated to be very good. (3) The results of the teacher's response questionnaire obtained 96% results which were declared very good and the results of the student response questionnaire in the limited trial obtained 83% results while in the wide trial the results obtained 82% which were stated to be very good.Keywords: Development; Comic Media; Determining Figures and Characteristics of Fairy TalesAbstrak Penelitian ini dilatarbelakangi bahwa guru saat menyampaikan materi menentukan tokoh dan watak dongeng dalam menggunakan media pembelajaran masih kurang bervariatif. Guru hanya menggunakan bahan ajar buku tematik dengan memperlihatkan gambar dan cerita mengenai materi tokoh dan watak dongeng, sehingga siswa kurang paham dalam memahami materi yang disampaikan. Rumusan masalah yaitu bagaimana kevalidan, keefektifan, respon guru dan siswa pada media komik materi menentukan tokoh dan watak dongeng untuk siswa kelas 4 sekolah dasar dalam penggunaannya sebagai media saat pembelajaran. Penelitian ini mengunakan metode penelitian Research and Development (R&D) dengan model ADDIE (Analyze, Design, Developmen, Implementation, dan Evaluation). Subjek penelitian ini adalah guru dan siswa kelas IV SDN Ngadi. Hasil dari penelitian pengembangan media komik adalah sebagai berikut: (1) Hasil validasi media komik rata-rata hasil sebesar 87,7% yang dinyatakan sangat valid. (2) Hasil efektifitas media komik pada uji coba terbatas mendapatkan 100% sedangkan uji coba luas mendapatkan 94,11%, berdasarkan hasil tersebut, media komik dinyatakan sangat baik. (3) Hasil angket respon guru diperoleh hasil 96% dinyatakan sangat baik dan hasil angket respon siswa pada uji coba terbatas diperoleh hasil 83% sedangkan pada uji coba luas diperoleh hasil 82% dinyatakan sangat baik.Kata Kunci: Pengembangan; Media Komik; Menentukan Tokoh dan Watak Dongeng